Immersive Media-Based Tourism Emerging Challenge of VR Addiction Among Generation Z - Saneinia, Saba; Zhou, Rongting; Gholizadeh, Ali; Asmi, Fahad (Frontiers in Public Health, 2022)
The virtual reality (VR) applications in entertainment and tourism industry have become growingly intense among generation Z. Interestingly, some pilot research on tourism studied concluded the positive impact of its flow experience on adoption of VR tourism, which is also driving the risk of immersive addictive. In the context of tourism and information and communication technology (ICT)-based innovation, there is a lack of immersive addictive behavior (IAB)-related literature. In addition, during the currently ongoing pandemic crisis, VR technology has gained particular importance in the tourism industry among generation Z. The present venture underlines the mechanism of IAB, investigates the VR addiction while underlining the cognitive abilities of individuals. This study applies empirical framework of cognitive–behavioral model. Results demonstrate that in the case of VR tourism, the immersive experience (presence and flow) determines the addictive behavior. Furthermore, VR imagery (VI), psychological curiosity (PC), and VR convenience (VRC) have significant influence on the VR presence and immersive flow. Moreover, the practical and theoretical implications have been discussed in the current research to prevent IAB.